Flotation separation behavior of chalcopyrite and sphalerite in the presence of locust bean gum. (November 2019) - Feng, Bo; Guo, Yutao; Zhang, Wenpu; Peng, Jinxiu; Wang, Huihui; Huang, Zhiqiang; Zhou, Xiaotong
Highlights: Locust bean gum has strong depression effect on sphalerite. The depression effect of locust bean gum on chalcopyrite is weak. Locust bean gum has greater influence on sphalerite surface properties. Locust bean gum adsorbed through interaction with the ZnOH or ZnO. Abstract: Locust bean gum was tested as a potential selective depressant in the flotation separation of chalcopyrite and sphalerite using potassium butyl xanthate (PBX) as collector. In single mineral flotation, locust bean gum depressed sphalerite, while chalcopyrite was floatable. This illustrated that locust bean gum could be used to separate chalcopyrite from sphalerite. Adsorption tests and zeta potential measurements indicated that locust bean gum can adsorb on the surfaces of both chalcopyrite and sphalerite, but the adsorption amount on sphalerite was higher than that on chalcopyrite. XPS analysis showed that locust bean gum adsorbed on the sphalerite surface through chemical interaction between ZnOH or ZnO on the sphalerite surface and hydroxyl groups of locust bean gum. Locust bean gum adsorbed more easily on the sphalerite surface, perhaps due to sphalerite being easier to oxidize than chalcopyrite.